Geophysical Studies in the Southwest Pacific : Primarily Studies of Crustal Structure between New Zealand and Antarctica - Falconer, Robin Keith Halcro (11668936) (1974)
Geophysical data - primarily magnetic field measurements, bathymetry, and seismicity data - are presented for the area between New Zealand and Antarctica from approximately 145[degrees]W to 155[degrees]E. The data are used to determine the structure of the Pacific-Antarctic boundary, the oceanic part of the Pacific plate and the area of intersection of the Indian, Pacific and Antarctic plates. In the southwest Pacific basin the magnetic anomalies are very clear and an extensive pattern of anomaly lineations with some offsets is mapped. The magnetic anomalies show that the uniform Pacific basin area formed between about 83 and 63 mybp. The Pacific-Antarctic boundary is shown to differ either side of about 175[degrees]W. To the east it is a relatively uniform aseismic spreading ridge, offset by some transform faults. West of 175[degrees]W, to 161[degrees]E, the boundary consists of a seismically active zone of disturbed bathymetry and magnetic anomalies striking about N.70[degrees]W. The zone, the Pacific-Antarctic fracture zone, probably consists of several fractures striking about N45[degrees]W. The area between the Pacific-Antarctic boundary and the southwest Pacific basin represents the interval 10 to -55 mybp, and only in the east are anomaly lineations clear. The Indian-Antarctic Pacific triple junction is near 61.5[degrees]S, 161[degrees]E and is a stable ridge-fault-fault junction; the Indian-Antarctic boundary being the ridge. Plate tectonics is applied to the area and the structure is shown to fit, and be explained by a different rotation pole for each of the major intervals indicated by the structure, i.e. 0-10 mybp, 10-63 mybp and 63-80 mybp. The poles, with rotation rates deduced from the magnetic anomalies, are used to reconstruct the position of New Zealand relative to Antarctica at 80 mybp. The two continents probably started to separate at close to 83 mybp. The times of the major changes of structure and plate movement in the area are shown to coincide with major plate movement changes in the southwest Pacific area and in the rest of the world. A new method for determining poles of rotation, based only on epicentre locations is presented, The method is applied to independently determine the Indian-Pacific, Pacific-Antarctic and Indian-Antarctic poles. The poles should form a consistent. set and they do. The method yields effectively instantaneous poles, is quantitative, and is applicable to most plate boundaries. Earthquake magnitude-frequency relationship b values for the plate boundaries in the area are determined. Comparisons with results from elsewhere indicate an association of high b with high temperature and conversely. Several factors which have previously been suggested as determining b value are shown to not be determinants. A revised and extended magnetic reversal time scale based on model studies of the southwest Pacific basin anomalies is presented. Other model studies indicate that a magnetized layer thickness of at least 2 km is probable. Variations of anomaly amplitudes are studied. A detailed study of the application of numerical correlation techniques to magnetic anomalies is presented. It is concluded that horizontal scale variations and discontinuities in profiles can be critical. Methods for over-coming some of the problems, and for determining quantitative error estimates, are. given. The methods, and conclusions, are applicable to any correlation problem.